PATHOGENESIS AND ETIOLOGY OF CHRONIC MYELOPROLIFERATIVE NEOPLASMS (CMPNS): A COMPREHENSIVE REVIEW - Jakhonov Azizbek Kholmirzaevich,; Matkarimova Dilfuza Saburovna, (TADQIQOTLAR, 2025)
Abstract Chronic myeloproliferative neoplasms (CMPNs) are a heterogeneous group of hematopoietic stem cell disorders characterized by the clonal proliferation of one or more myeloid lineages. The main subtypes include chronic myeloid leukemia (CML), polycythemia vera (PV), essential thrombocythemia (ET), and primary myelofibrosis (PMF).  These  disorders  share  common  pathogenic  mechanisms,  often  involving mutations in genes such as JAK2, CALR, and MPL, leading to dysregulated signaling pathways  and  abnormal  hematopoiesis.  This  review  summarizes  the  current understanding  of  the  etiology  and  pathogenesis  of  CMPNs,  highlighting  molecular mechanisms,  clinical  manifestations,  diagnostic  criteria,  and  potential  therapeutic targets.